Role of Fatherhood to Build the Linguistic Identity of Daughters in Nepal - Mainali, Sudha (Bhashalok भाषालोक, 2026)
This study investigates the profound and varied impact of fatherhood practices on the childhood identity formation and language learning paths of daughters in the patriarchal socio-cultural setting of Nepal. It aims to explore the stable academic gap to understand how paternal engagement and socio-cultural milieu enable the daughters’ educational and professional development strands. The study applies qualitative research methods underpinning narrative inquiry. The study utilizes Norton’s (2013) theory of Investment from Language learning and Identity. The study has selected six English teachers as participants from Kathmandu, Bhaktapur, and Lalitpur. It has used in-depth interviews to gather rich lived experiences and detailed narratives of participants. It attempts to identify the traditional, emotionally distant father and the responsible, actively involved father who champions gender parity. The study reveals a direct correlation between paternal support and his commitment and communication style, and daughters’ self-worth. This self-concept fundamentally mediates daughters' language learning practices and their capacity to become strongly educated and professional in the imagined community. The main contribution is that progressive fatherhood can facilitate daughters by providing higher parental economic status, confidence, and challenging social barriers, thereby promoting self-autonomy. The study asserts that perceiving women’s linguistic and professional empowerment is a fundamental paradigm shift in the patriarchal context.